2019
DOI: 10.1128/jvi.00371-19
|View full text |Cite
|
Sign up to set email alerts
|

Differential Dynamics of Regulatory T-Cell and Th17 Cell Balance in Mesenteric Lymph Nodes and Blood following Early Antiretroviral Initiation during Acute Simian Immunodeficiency Virus Infection

Abstract: Increased frequencies of immunosuppressive regulatory T cells (Tregs) are associated with gut lymphoid tissue fibrosis and dysfunction which, in turn, contribute to disease progression in chronic simian immunodeficiency virus/human immunodeficiency virus (SIV/HIV) infection. Mesenteric lymph nodes (MLNs), which drain the large and small intestine, are critical sites for the induction and maintenance of gut mucosal immunity. However, the dynamics of Tregs in MLNs are not well understood due to the lack of acces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 63 publications
7
33
0
Order By: Relevance
“…Also, we compared SR to SE to reveal the host-virus interaction in the context of virus-detectable host immunity status. In each single stage, our findings were highly consistent with previous studies (Hunt et al, 2008;Molina-Pinelo et al, 2009;Robbins et al, 2009;Hunt, 2012;Vandergeeten et al, 2012;Wittkop et al, 2013;Osuji et al, 2018;Yero et al, 2019;Antar et al, 2020;Bordoni et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…Also, we compared SR to SE to reveal the host-virus interaction in the context of virus-detectable host immunity status. In each single stage, our findings were highly consistent with previous studies (Hunt et al, 2008;Molina-Pinelo et al, 2009;Robbins et al, 2009;Hunt, 2012;Vandergeeten et al, 2012;Wittkop et al, 2013;Osuji et al, 2018;Yero et al, 2019;Antar et al, 2020;Bordoni et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…Using eight SIV mac239infected rhesus macaques, we longitudinally tracked host immunosenescence and immunoactivation by comparing SS to SN and SR to SE. Our ndings were consistent with previous studies [21][22][23][24][25][26][27][28] , and comparing SS to SN, we showed accelerated host immunosenescence and elevated low-level in ammation at the same time as SIV expression was undetectable. In comparing SR to SE, we showed accelerated host immunoactivation with elevated in ammation that correlated with increased SIV replication during rebound 29,30 .…”
Section: Discussionsupporting
confidence: 93%
“…As a result, HIV and SIV infections are characterized by a switch from Th1 to Th2 phenotype (56), and a significant depletion of Th17 cells is observed among circulating lymphocytes throughout the infection (7). HIV-1 can also infect Tregs (57), and, although reduced (7,(58)(59)(60), stable, and increased (61,62) absolute circulating Treg counts have all been reported during chronic infections, a decreased Th17/ Treg ratio is commonly observed in pathogenic infections and was linked to immune activation and disease progression (7,62). Furthermore, a selective depletion of circulating CD4 + T cells with gut homing potential (i.e., expressing the a4b7 integrin) preferentially occurs in untreated PWH (63) and in SIV-infected RMs in which those cells are selectively infected in the first days of infection (8).…”
Section: Cd4 + T-cell Depletion In Pathogenic Hiv/siv Infections Circulation and Lymph Nodesmentioning
confidence: 99%
“…Furthermore, Th17 cells were also restored in patients receiving ART, especially in those in which therapy was initiated very early in infection (85). However, Th17/Treg ratio remained reduced, as Treg cell counts in lymph nodes and in GALT did not return to baseline levels in PWH receiving ART (60,61), which might be due to the residual viral replication and immune activation in the GALT of those patients (219).…”
Section: Restoration Of Cd4 + T Cells During Artmentioning
confidence: 99%
See 1 more Smart Citation